Prospects for monetary cooperation in East Asia - Yung Chul Park; Chi-Young Song (Asian Development Bank Institute (ADBI), 2011)
The purpose of this paper is to reexamine the exchange rate policy of the Republic of Korea, and its role in promoting financial and monetary cooperation in East Asia in the wake of the 2008 global financial crisis. The Republic of Korea would not actively participate in any discussion of establishing a regional monetary and exchange rate arrangement as it is expected to maintain a weakly managed floating regime. The People's Republic of China (PRC) has been fostering the yuan as an international currency, which will lay the groundwork for forming a yuan area among the PRC; the Association of Southeast Asian Nations (ASEAN); Hong Kong, China; the PRC; and Taipei, China. Japan has shown less interest in assuming a greater role in East Asia's economic integration due to deflation, a strong yen, slow growth, and political instability. Japan would not eschew free floating. These recent developments demand a new modality of monetary cooperation among the Republic of Korea, Japan, and the PRC. Otherwise, ASEAN+3 will lose its rationale for steering regional economic integration in East Asia.
Keywords: F3; F4; 330; Finanzmarktkrise; Flexibler Wechselkurs; Südkorea; Handelsregionalismus; Internationale wirtschaftspolitische Koordination; Wechselkurspolitik; Ostasien